SME-University internship unlocked opportunities for undergraduates to offer business consultation service - UMP, PNC
Universiti Malaysia Pahang (UMP)’s Entrepreneurship Centre, SME Corp Malaysia and Higher Education Ministry organised SME-University Internship programme for the first time that involved 24 undergraduates representing four consultation groups.